2019
DOI: 10.3389/fmicb.2019.01657
|View full text |Cite
|
Sign up to set email alerts
|

Commonality of Multidrug-Resistant Klebsiella pneumoniae ST348 Isolates in Horses and Humans in Portugal

Abstract: Multidrug-resistant (MDR) Klebsiella pneumoniae is considered a major global concern by the World Health Organization. Evidence is growing on the importance of circulation of MDR bacterial populations between animals and humans. Horses have been shown to carry commensal isolates of this bacterial species and can act as human MDR bacteria reservoirs. In this study, we characterized an extended-spectrum β-lactamase (ESBL)-producing K. pneumoniae sequence type (ST) 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 39 publications
(46 reference statements)
1
18
1
Order By: Relevance
“…The present study demonstrates that broad-spectrum cephalosporin-resistant members of the genus Klebsiella are present in the Austrian horse population, although the prevalence in clinical samples seems to be low. These findings are in accordance with previous studies describing the presence of these particular bacteria in horse populations of other countries [4,[6][7][8][9][10]. Moreover, a previous study carried out in 2018 on clinical samples from Austrian patients reported 8.4% of K. pneumoniae isolates as resistant to third-generation cephalosporins [23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study demonstrates that broad-spectrum cephalosporin-resistant members of the genus Klebsiella are present in the Austrian horse population, although the prevalence in clinical samples seems to be low. These findings are in accordance with previous studies describing the presence of these particular bacteria in horse populations of other countries [4,[6][7][8][9][10]. Moreover, a previous study carried out in 2018 on clinical samples from Austrian patients reported 8.4% of K. pneumoniae isolates as resistant to third-generation cephalosporins [23].…”
Section: Discussionsupporting
confidence: 92%
“…Contrarily, there is still a scarcity of information on broad-spectrum cephalosporin-resistant K. pneumoniae and members of the genus Klebsiella isolated from horses and other domestic animals. To date, only a few equine broad-spectrum cephalosporin-resistant Klebsiella have been isolated and characterized [4,[6][7][8][9][10]. Recent studies reported that some of the characterized resistant K. pneumoniae isolates of equine origin were human-associated multidrug-resistant (MDR) K. pneumoniae [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…Klebsiella spp. is a normal intestinal bacteria in horses [1] and is ubiquitous in the environment [2]. However, some studies have reported Klebsiella spp.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have reported Klebsiella spp. as a causal agent for infections in horses, such as mares with metritis and cervicitis, foals with septicemia and pneumonia [3], and pneumonia in adult horses [2], and disease severity depends on the pathogenicity of the strains [1]. In the horse industry, about 25%-60% of economic losses are caused by endometritis, and Klebsiella pneumoniae was reported as one of the causal infections that can be transmitted through the venereal route [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation